Civil society organizations and the promotion of democracy in the Nigeria’s Fourth Republic - Muhammad, Surajo Yahaya (2020)
To promote good governance and sustainable development, democracy and its tenants must to be in place, promoted and sustained. In Nigeria, there has been different regime after the return of civilian government in the fourth republic. Democracy appeared to find its place in Nigeria, but absence of political will, rule of law and inability of the government at various level to regard civil society organizations as important partner in the promotion of democracy has retarded the country’s ability to attain good governance, effective and efficient services to its citizens. Being an important pillar in the democratic process of modern society, and in order to effectively enhance their roles in the promotion of the democratic process, the paper attempted to look at possible ways in which civil society organizations can organize and mobilize themselves to effectively work with the government in promoting democracy and thereby, ensures sustainable development in Nigeria. The paper relied on document analysis as a source of relevant secondary data, and thematic analysis in analysing the data through themes and sub-themes in accordance with the central ideas of the paper. The discussion was situated within the framework of structural-functionalism theory. The findings of the paper reveals that civil society organizations, being actor in Nigeria’s democratic campaign process particularly in the area of anti-corruption, rule of law, respect for fundamental human rights has greatly helped the promoting democracy in Nigeria. The finding also reveals that civil society organizations are partner for development in any modern society through mobilization and voter education. The paper recommends the urgent need for civil society groups to understand that the need for unity by forming a multi-stakeholder mass movement in order to contribute towards democratic promotion particularly in the area of promoting democracy. It also recommends the need for a decentralized structure across the country.